(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This paper focuses on some small but possibly significant aspects of the pre-Roman languages of the Iberian Peninsula on the basis of the study of ancient, medieval and modern toponyms from Spain. Particularly, the examination of medieval documentation —extensive but often obliterated— can sometimes contribute to resolving etymological problems or to assigning a toponym to one or another ancient Hispanic language with greater confidence. This paper examines the implications that toponyms documented in the medieval period, such as Asilancia, Barchilona, Ciesçam, Esleniana, Gil, Lauro, Lausa, Quer, Resubius, and Tutanca, may have for our understanding of pre-Roman toponymy and, in general, for a better understanding of the pre-Roman languages of the Iberian Peninsula.